Perlindungan Hukum Bagi Korban Tindak Pidana Kekerasan Dalam Rumah Tangga (KDRT) - Vidi Pradinata (UNISSULA Semarang, 2020)
In Indonesia there are many criminal acts, one example is the violence that often occurs in a household or commonly called the act of violence in the household. Households should be a shelter for all family members. However, in reality many households become places of suffering and torture because of violence. Domestic violence is a problem that can not be overcome by using the Criminal Code. Because in the Criminal Code only regulate the general form of violence. So that made Law No.23 Year 2004 about abolition of violence in the household. In handling cases of domestic violence is different from the handling of other criminal cases, and domestic violence is a crime complaint where the victim can revoke his report when it has considered everything for the good of his family. Household is a very privacy because household should not be public consumption hence handling of cases of KDRT usually experience barrier. Where a household should be a refuge for members of his family but often violence caused by several factors. In solving the domestic violence problem, it lacks sufficient and specific protection, and even the main problem relating to law focuses on the absence of laws that specifically provide protection for victims in domestic violence in Indonesia. In this writing may be many shortcomings. Therefore, the authors expect constructive suggestions and criticismsKeywords: Legal Protection, Victims, Criminal Violence in the Household